“Self-Portrait” and the Issues of the Visual in the Russian Poetry of the 20th Century - Malkina, Viktoriia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The paper analyses visual poetics in a number of poems entitled “Self-portrait”. The author construes the visual in literature as a category of poetics which assumes the visibility of the inner world of the poem for the lyrical subject and for the reader. The visual in the lyric poetry can be expressed in various ways, including allusions to the genres of visual arts, for example, to self-portraiture. The topic undertaken is relevant, given the currently growing interest in intermediality in literature in general and in poetry in particular. What is new about the present research is that poetic self-portraits are considered here from the point of view of visual poetics. The main purpose of the paper is to analyse the ways in which the lyrical subject visually represents his or her own image. The following aspects are touched upon: the interaction of poetry and painting, the common and the differentiating features of a pictorial and a lyrical self-portrait; the use of visual details; the subjective structure of poems and the lyrical plot. There is also an attempt to build a typology of poetic self-portraits, depending on how the lyrical subject sees himself/herself as another. The material of the study includes poems by Aleksandr Kushner, Ilya Selvinsky, Andrei Voznesensky, Osip Mandelshtam, Konstantin Bolshakov, Valentin Katarsin, Nikolai Rylenkov, and others.